The Influence of Work Environment, Work Culture, and Individual Characteristics on Employee Performance - Muhammad Wahyu; Kuswandi Kuswandi; Sri Rahayu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the manufacturing industry such as PT. Anugrah Aneka Box, employee performance is a crucial aspect because it has a direct impact on productivity, product quality, and operational efficiency. This study is motivated by the increasing demands for product and service quality in the manufacturing sector. Optimal employee performance not only ensures smooth production processes, but also affects customer satisfaction and the company's reputation. This study aims to analyze the influence of Work Environment, Work Culture, and Individual Characteristics on Employee Performance at PT. Anugrah Aneka Box in Gresik, East Java. The research sample consisted of all employees of the Corrugated Paper Box division, totaling 89 people. Data collection techniques were carried out through questionnaires, while data measurement used a Likert scale. Data were analyzed using multiple linear regression techniques. The results of the study showed that partially, Work Environment, Work Culture, and Individual Characteristics each had a significant effect on Employee Performance. Simultaneously, these three variables also had a significant effect on Employee Performance at PT. Anugrah Aneka Box in Gresik, East Java.